TOURISM IS ONE OF THE IMPORTANT PILLARS OF THE GREEN ECONOMY - Dadakhanov Shukhrat Abdumalikovic (Scholar Express Journals, 2024)
In the article, taking into account the market requirements and the specific features of the economic situation of our republic, the opportunities for the development of the tourism sector through the greening of the economy, the current problems of the rational use of resources are considered. The negative consequences of the use of natural resources in tourism are identified. Based on the development of new methods and digital technologies, issues related to achieving the desired effect are considered. In addition, the main principles of rational use of resources in the development of tourism sectors in the transition to a green economy were proposed. The real situation of green economy and tourism in Uzbekistan is analyzed. Modernization of the tourism system through the expansion of green space, the processing of renewable resources, which allows reducing the loss of natural resources and increasing their productivity, is presented.
Keywords: greening of the economy; conference; all branches; preservation of natural resources